Istikhdāmu al-Bithāqāt at-Ta’līmiyyah fī Tarqiyati al-Kafā`ati al-Mufradāt ladai at-Thullābi fī Madrasati Sabīlu at-Thayyib Pasuruan - Hidayah, Zia Haninatul; Asrori, Imam; Ahsanuddin, Mohammad (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2023)
Vocabulary is one of the language elements that must be owned and mastered by foreign language learners, including Arabic. This requires teachers to be more creative in choosing and using vocabulary teaching media to achieve the best learning results. Flashcards are one of the easiest and most effective media for learning mufrodat. This study aims to determine the effect of flashcards media on the mastery of Arabic vocabulary of Sabiluth Thoyyib Senior High School students. The sample of this research amounted to 20 students. This research is quasi-experimental research using t-test. This study used a one group pre-test and post-test design. The instruments in this study were pre-test and post test questions. In the t-test results using Paired sample t-test analysis. With the help of SPSS 22.0 for windows software. The results showed that there was a positive effect of flashcards on the mastery of Arabic vocabulary. Obtained a significant value of 0.000. It is known that the results (Sig. (2-tailed)) of 0.000 <0.05, it can be concluded that learning by using flashcards has an effect in improving mastery of Arabic mufrodat. So, the use of flashcard media in learning Arabic to improve vocabulary skills has a positive effect on Sabiluth Thoyib high school students. Therefore, we can use this media in learning Arabic with various learning methods so that learning Arabic becomes effective and very interesting, especially in learning vocabulary. المفردات إحدى عناصر اللغة التي يجب أن يمتلكها ويتقنها متعلمي اللغات الأجنبية ، بما في ذلك اللغة العربية. وهذا يتطلب من المعلمين أن يكونوا أكثر إبداعًا في اختيار واستخدام وسائل تعليم المفردات من أجل تحقيق أفضل نتائج التعلم. تعد البطاقات التعليمية من أسهل الوسائط وأكثرها فاعلية لتعلم المفردات. تهدف هذه الدراسة إلى تحديد تأثير وسائط البطاقات التعليمية في  ترقية الكفاءة  المفردات العربية لدى طلاب في المدرسة سبيل الطيب الثانوية باسوروان. و عدد عينة البحث 20 تلميذا وتلميذة. هذا البحث هو بحث شبه تجريبي باستخدام  الإختبار – t . وقد كان التصميم لهذا البحث مجموعة قبل الإختبار و بعده (pretest-post-test). الأدوات في هذه الدراسة كانت أسئلة الاختبار القبلي والبعدي. في نتائج اختبار t باستخدام تحليل اختبار t للعينة المزدوجة. بمساعدة SPSS 22.0 لبرنامج . windows أظهرت النتائج وجود تأثير إيجابي للبطاقات التعليمية في الترقية المفردات. تم الحصول على قيمة دلالة قدرها 0.000. من المعروف أن نتائج (علامة (2-tailed)) بقيمة 0.000 <0.05 ،  و الاستنتاج أن التعلم باستخدام البطاقات التعليمية له تأثير في تحسين إتقان  المفردات العربية. لذا فإن استخدام وسائط البطاقات التعليمية في تعلم اللغة العربية لتحسين الكفاءة المفردات له تأثير إيجابي على طلاب مدرسة سبيل الطيب الثانوية باسوروان . لذلك يمكننا استخدام هذه الوسيلة في تعلم اللغة العربية بأساليب تعلم مختلفة حتى يصبح تعلم اللغة العربية فعالاً وممتعًا للغاية ، خاصة في تعلم المفردات.